Assessment of water quality in disease burdened industrializing town of mid hills of North India - Singh, Ajay K.; Bhardwaj, Satish K. (International Journal of Research in Medical Sciences, 2023)
Background: Anthropogenic activities associated with rapid urbanization and industrialization have deteriorated the water quality across the world. Rampant industrialization and poor water, sanitation and hygiene in an industrializing town of northern India necessitated the assessment of drinking water in the region. Methods: The study of physico-chemical parameter of the water and water quality index of the most commonly used ten drinking water sources in 2017-2018 was undertaken. Grab water samples were collected during monsoon, the rainy season (June, July and August) and post monsoon (September, October and November) during the years 2017 and 2018 by following the standard procedures. Weighted arithmetic index method was used for the water quality index (WQI) analysis. Results: Pooled analysis inferred water pH, temperature, total dissolved solids and carbonated oxygen demand to be within, whereas, electrical conductivity (91.00-431.50 µS/cm), turbidity (1.00-4.30 mg/l), dissolved oxygen (6.53-7.23 mg/l) and biological oxygen demand (6.12-7.62 mg/l), exceeding the Bureau of Indian standards permissible limits. Calcium, nitrate, chlorides and zinc were within limits, magnesium concentrations (9.16-29.35 mg/l) were below whereas lead (0.06-0.62 mg/l), chromium (0.01-0.12 mg/l), cadmium (0.00-0.25 mg/l) and mercury (0.00-0.08 mg/l) were above the standards. WQI was above 50 in all the drinking water sources. Conclusions: Water was of poor quality and unsuitable for drinking purposes, indicating alarming water pollution. WQI of the various drinking water sources of the region deteriorated more in the monsoon season as compared to the post monsoon season.